Neighbourhood expansion and urban livability in Seremban municipality area, Malaysia - Shaharudin Idrus,; Abdul Samad Hadi,; Abdul Hadi Harman Shah,; Ruslan Rainis, (Environmental Management Society, Malaysia, 2010)
The approach taken in this article is looks at change influencing the understanding of the phenomenon. A pattern of change that seems smooth and linear at a smaller scale might yield fluctuations that can only be perceived at a larger scale, closer to ground zero. Viewing change at the local level can provide tipping points and critical transitions that are hidden in the more general pattern and such detailed incremental approach to urbanization allows one to understand why, given the same set of drivers, some areas seem to prosper while others lag far behind. This provides an alternative viewpoint to the traditional market oriented aggregate analysis or the hedonistic explanation to growth. This article views urban expansion as a culmination of local level activities that emerge into a complex network of urban growth. This urban expansion in Malaysia can be traced back as early as the 1890, and the transition issues in Malaysian urbanization include the phases of the urbanization experience, the rise of mega urban regions, and the need for a new way of viewing the processes through the daily decision makings carried out by individuals in the city. These decisions eventually produce the spatial-temporal patterns of life in the Malaysian cities. These are then visualized in the patterns of land use, housing spread, commercial use and others. The patterns are dynamic, often time changing in response to changing drivers. The article argues that effective planning for the urban expansion needs to be viewed from the local scene. The various local scenarios are then built up incrementally over space and time to produce a regionwide explanation of urbanization. This is, again, an alternate viewing of regional analysis that traditionally looks at the local as merely being a component of the larger region, differentiated by local attributes that create local shifts that skew its share of the regional trend. Housing neighbourhood in the Seremban Municipality area is uses as an illustration of the urban expansion